Lead-carbon battery negative electrode material for power storage and preparation method thereof

By directly adding sulfate to the negative electrode material of lead-carbon battery and introducing adhesives and porous ceramics, the problem of poor performance of lead-carbon battery during high current charging and discharging is solved, and the high- and low-temperature charging and discharging performance of the battery is improved. .

CN118943307BActive Publication Date: 2025-02-07ZHEJIANG CHAOWEI POWER
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411415435.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-02-07
Estimated Expiration
2044-10-11

AI Technical Summary

Technical Problem

The existing lead-carbon batteries have poor performance during high current charging and discharging, making it difficult to meet the requirements of power energy storage systems for high-temperature and low-temperature charging and discharging performance.

Method used

By directly adding sulfate during mixing and mixing, the reaction is heated, a stable ratio is formed, and adhesives and porous ceramics are introduced to improve the plasticity and conductivity of the negative electrode material and enhance the diffusion ability of sulfuric acid.

Benefits of technology

It improves the performance of lead-carbon batteries during charging and discharging of high currents, enhances the battery's high- and low-temperature charging and discharging capabilities, and is suitable for power energy storage systems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118943307B_ABST
    Figure CN118943307B_ABST
Patent Text Reader

Abstract

The present invention relates to a negative electrode material of a lead-carbon battery for power energy storage, comprising 100 parts of lead powder, 6-10 parts of sulfate, 1-2 parts of mixed material, 0.5-1 parts of CMC adhesive and 8-15 parts of water; the mixed material comprises 1-3 parts of microporous ceramic, 2-5 parts of conductive carbon black, 0.5-1 parts of conductive fiber, 2-5 parts of lead powder, 3-8 parts of nucleating agent, 1-3 parts of dispersant and 0.5-1 parts of activated carbon; the present invention also relates to a preparation method for preparing the negative electrode material of a lead-carbon battery for power energy storage, comprising a filling process, a material mixing process, a mixing process and a paste process. The present invention solves the problem that the existing lead-carbon battery has poor performance during high current charging and discharging.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lead-carbon batteries, and in particular to a lead-carbon battery negative electrode material for power energy storage and a manufacturing method thereof. Background Art

[0002] Lead-carbon battery is a type of lead-acid battery commonly used in the power industry. Compared with traditional lead-acid batteries, it has higher requirements in basic characteristics including voltage, capacity, charge acceptance, fluidization resistance, cycle life, etc. Lead-carbon battery is a battery with lead dioxide as the positive electrode, lead-carbon composite electrode as the negative electrode, and sulfuric acid solution as the electrolyte. The negative electrode material of the lead-carbon battery generally contains lead powder, dispersant, nucleating agent, conductive material and other components. At present, the energy storage system in the power industry is mainly to shave peaks and fill valleys. The valley electricity with low price during off-peak hours is stored in batteries, and then the electricity in the energy storage battery is released through the substation system during the peak electricity period of the next day, so as to achieve the purpose of cost reduction.

[0003] The patent document with patent number CN108630937A discloses a lead-carbon battery negative electrode lead paste and a negative electrode plate. The lead-carbon battery negative electrode lead paste is prepared from the following raw materials in a weight distribution ratio: 100 parts of ball-milled lead powder, 0.5-10 parts of modified high specific surface area carbon material, 0.05-5 parts of short-cut carbon fiber, 0.05-0.5 parts of PhosmerPE, 0.5-3 parts of ultrafine barium sulfate, 0.5-2 parts of lignin sulfonate, 0.5-2 parts of humic acid, 10-20% of water by mass of the lead powder, and 10-15% of sulfuric acid aqueous solution by mass of the ball-milled lead powder. The negative lead paste is then evenly coated on the negative grid, and then 1.0-1.2 mol / L of dilute sulfuric acid is sprayed on the surface of the negative grid coated with the negative lead paste, and then the negative grid coated with the negative lead paste and sprayed with dilute sulfuric acid is placed in a temperature of 45-70°C and a relative humidity of 85-99% for curing for 36-60 hours, and after curing, the negative plate is used as a negative plate, and the negative plate is placed in an electrolyte for chemical formation, and after chemical formation, it is used as a finished lead-carbon battery negative plate. The battery made of the plate of the present invention has the advantages of high hydrogen evolution overpotential and long cycle life.

[0004] However, the working environment of the power energy storage system generally requires 0-45°, so its high-temperature charging and discharging performance and low-temperature charging and discharging performance requirements are relatively high. When the power energy storage system is working, it requires instantaneous high-power charging and discharging according to the client's usage. During actual use, the inventor found that the existing lead-carbon battery has poor high-current charging and discharging performance. Therefore, how to develop a new negative electrode lead paste to improve the high-current charging and discharging performance of lead-carbon batteries is an urgent problem to be solved by technical personnel in this field. Summary of the invention

[0005] The purpose of the present invention is to solve the shortcomings of the prior art. By directly adding sulfate during mixing and preparing, the reaction heat can be avoided. A stable ratio can be formed according to the process requirements, which is convenient for preparation. At the same time, an adhesive and porous ceramics are introduced. Under a certain amount of water, the adhesive can improve the plasticity of the negative electrode material, which is convenient for filling and coating on the plate. The porous ceramics filled with conductive carbon black can make the negative electrode material filled on the plate have a higher porosity and a good conductive effect, which is conducive to the diffusion of sulfuric acid during battery charging and discharging. Thereby solving the problem that the existing lead-carbon battery has poor performance during high current charging and discharging.

[0006] In view of the above technical problems, the technical solution adopted is as follows: A lead-carbon battery negative electrode material for power energy storage, comprising:

[0007] 100 parts of lead powder, 6-10 parts of sulfate, 1-2 parts of mixed materials, 0.5-1 parts of CMC adhesive and 8-15 parts of water;

[0008] The mixed material comprises 1-3 parts of microporous ceramics, 2-5 parts of conductive carbon black, 0.5-1 parts of conductive fibers, 2-5 parts of lead powder, 3-8 parts of nucleating agents, 1-3 parts of dispersants and 0.5-1 parts of activated carbon.

[0009] Preferably, the sulfate comprises 3-8 parts of tribasic lead sulfate and 4-15 parts of tetrabasic lead sulfate.

[0010] Preferably, the microporous ceramic is a spherical porous ceramic, the diameter of the microporous ceramic is 95um-105um, and the pore size of the micropores on the microporous ceramic is 5um-50um.

[0011] Preferably, the nucleating agent is barium sulfate, and the dispersing agent is sodium lignin sulfate.

[0012] The present application also provides a preparation method for preparing the above-mentioned lead-carbon battery negative electrode material for power energy storage, comprising the following steps:

[0013] Step 1: a filling process, mixing the microporous ceramic and the conductive carbon black, and evenly filling the conductive carbon black into the micropores of the microporous ceramic, and then adding the conductive fiber to evenly mix the three into a first mixture;

[0014] Step 2: a mixing process, wherein the lead powder, the nucleating agent, the dispersant and the activated carbon are uniformly mixed into a second mixed material, and then the first mixed material and the second mixed material are uniformly mixed into the mixed material;

[0015] Step 3: Mixing process: take lead powder and put it into a vacuum paste machine together with the mixed material, then add sulfate and adhesive, and start stirring for 10 minutes to mix;

[0016] Step 4: Paste mixing process. After the mixing is completed, water is slowly added into the vacuum paste mixing machine within 3 minutes and the plasticity is adjusted after continuous stirring for 5 minutes to form the lead paste of the negative electrode material of the lead-carbon battery for power energy storage, which is then filled and used.

[0017] Preferably, in step one and step two, the first mixture and the second mixture are mixed in the same mixing device, and a mixing chamber and a temporary storage chamber are formed in the mixing device. After the first mixture is mixed in the mixing chamber, it is temporarily stored in the temporary storage chamber. After the second mixture is mixed in the mixing chamber, the first mixture in the temporary storage chamber enters the mixing chamber again for mixing.

[0018] Preferably, in step one, the microporous ceramic and the conductive carbon black are fluidized and mixed and vibrated to fill the conductive carbon black into the micropores of the microporous ceramic via vibration while mixing, and the fluidized first mixture is convenient for collection and temporary storage in the temporary storage chamber.

[0019] Preferably, in step 2, lead powder, nucleating agent, dispersant and activated carbon are mixed by stirring to achieve mixing while preventing the materials from being lifted up and entering the temporary storage chamber in large quantities. The first mixture and the second mixture are mixed by stirring and fluidizing to achieve rapid and uniform mixing of the mixed materials.

[0020] Preferably, in step one, the microporous ceramic is subjected to dust removal before being mixed with the conductive carbon black to remove dust in the microporous ceramic.

[0021] Preferably, in step 2, the lead powder, nucleating agent, dispersant and activated carbon are ground and then mixed.

[0022] Beneficial effects of the present invention:

[0023] (1) In the present invention, by directly adding sulfate during mixing and preparing, heat generation by reaction is avoided, and a stable ratio can be formed according to process requirements, which is convenient for preparation. At the same time, the adhesive and porous ceramic are introduced. Under a certain amount of water, the adhesive can improve the plasticity of the negative electrode material, which is convenient for filling and coating on the electrode plate. The porous ceramic filled with conductive carbon black can make the negative electrode material filled and coated on the electrode plate have a higher porosity and a good conductive effect, which is conducive to the diffusion of sulfuric acid during charging and discharging of the battery;

[0024] (2) In the present invention, the microporous ceramic is set to be a spherical porous ceramic, and the size of the microporous ceramic and the micropores thereon are limited to a suitable range, so as to facilitate the filling and adhesion of the conductive carbon black while avoiding affecting the plasticity of the negative electrode material;

[0025] (3) In the present invention, by setting the nucleating agent to be barium sulfate and the dispersing agent to be sodium lignin sulfate, the barium sulfate can improve the porosity of the negative electrode material on the electrode plate, and the sodium lignin sulfate can improve the dispersion performance of the negative electrode material on the electrode plate, promote the diffusion of the electrolyte, improve the utilization rate of the active material, limit the growth space of the lead sulfate particles, and reduce the "sulfation" effect, thereby further improving the charge and discharge performance and overall performance of the battery;

[0026] In summary, lead-carbon batteries made of negative electrode materials have good performance when charged and discharged at large currents, and are particularly suitable for the field of lead-carbon battery technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0028] Figure 1 This is a schematic diagram of the structure of the microporous ceramic provided by the present invention.

[0029] Figure 2 A three-dimensional diagram of a mixing device provided by the present invention.

[0030] Figure 3 A three-dimensional cross-sectional view of a mixing device provided by the present invention.

[0031] Figure 4 A schematic structural diagram of the vibration assembly provided by the present invention.

[0032] Figure 5 This is a schematic structural diagram of the stirring assembly provided by the present invention.

[0033] Figure 6 This is a schematic structural diagram of the flow guide assembly provided by the present invention.

[0034] Figure 7 A cross-sectional view of a mixing device provided by the present invention.

[0035] Figure 8 The present invention provides Figure 7 A partial enlarged view of point A in the middle.

[0036] Fig. 9 This is a schematic structural diagram of the screening mechanism provided by the present invention.

[0037] Fig.10 The present invention provides Fig. 9 A partial enlarged view of point B in the middle.

[0038] Fig.11A schematic flow chart of a method for producing a negative electrode material for a lead-carbon battery for electric energy storage provided by the present invention. DETAILED DESCRIPTION

[0039] The technical solutions in the embodiments of the present invention are clearly and completely described below in conjunction with the accompanying drawings.

[0040] Embodiment 1

[0041] like Figure 1 As shown, a lead-carbon battery negative electrode material for power storage includes:

[0042] 100 parts of lead powder, 6-10 parts of sulfate, 1-2 parts of mixed materials, 0.5-1 parts of CMC adhesive and 8-15 parts of water;

[0043] The mixed material comprises 1-3 parts of microporous ceramic, 2-5 parts of conductive carbon black, 0.5-1 parts of conductive fiber, 2-5 parts of lead powder, 3-8 parts of nucleating agent, 1-3 parts of dispersant and 0.5-1 parts of activated carbon.

[0044] In this embodiment, by directly adding sulfate during mixing and preparing to avoid reaction heat, a stable ratio can be formed according to process requirements for easy preparation, and adhesives and porous ceramics are introduced at the same time. Under a certain amount of water, the adhesive can improve the plasticity of the negative electrode material, making it easier to fill it on the plate. The porous ceramics filled with conductive carbon black can make the negative electrode material filled on the plate have a higher porosity and a good conductive effect, which is beneficial to the diffusion of sulfuric acid during battery charging and discharging.

[0045] Furthermore, the sulfate includes 3-8 parts of tribasic lead sulfate and 4-15 parts of tetrabasic lead sulfate.

[0046] In this embodiment, since the amount of sulfuric acid added in the automatic paste machine and the speed of addition will cause different exothermic reactions between sulfuric acid and lead powder, different ratios of tribasic lead sulfate and tetrabasic lead sulfate will be formed at different temperatures, which is difficult to control. By directly adding a certain ratio of tribasic lead sulfate and tetrabasic lead sulfate, a stable ratio is formed, which is convenient for mixing.

[0047] Further, if Figure 1 As shown, the microporous ceramic is a spherical porous ceramic, the diameter of the microporous ceramic is 95um-105um, and the aperture of the micropores 6 on the microporous ceramic is 5um-50um.

[0048] In this embodiment, the structure and size of the microporous ceramic are appropriate to avoid affecting the plasticity of the negative electrode material, and the pore size of the micropores 6 on the microporous ceramic is appropriate to facilitate the filling and adhesion of the conductive carbon black.

[0049] Furthermore, the nucleating agent is barium sulfate and the dispersing agent is sodium lignin sulfate.

[0050] In this embodiment, barium sulfate can increase the porosity of the negative electrode material on the electrode plate, thereby further improving the charge and discharge performance of the battery. Sodium lignin sulfate can improve the dispersion performance of the negative electrode material on the electrode plate, promote electrolyte diffusion, increase the utilization rate of active substances, limit the growth space of lead sulfate particles, and reduce the "sulfation" effect, etc., which significantly improves the overall performance of the electrode and battery.

[0051] Embodiment 2

[0052] like Figure 1-Figure 3 As shown, a mixing device is used to mix materials and produce mixed materials, comprising:

[0053] A mixing tank 1, a partition cover 2 disposed in the mixing tank 1 and separating the mixing tank 1 into a mixing chamber 11 and a temporary storage chamber 12, a mixing mechanism 3 disposed at the bottom of the mixing tank 1 and used for mixing materials, a grinding mechanism 5 connected to a feed inlet 13 of the mixing tank 1 and used for grinding materials, and a screening mechanism 4 disposed inside the mixing tank 1 and used for screening materials;

[0054] The mixing mechanism 3 includes a vibration component 31 arranged at the bottom of the mixing tank 1 and used to vibrate the material, a stirring component 32 arranged at the bottom of the mixing chamber 11 and used to stir the material, a fluidizing component 33 arranged at the bottom of the mixing chamber 11 and used to fluidize the material, and a guide component 34 arranged on the partition cover 2 and used to guide the material into the mixing chamber 11 or the temporary storage chamber 12.

[0055] In this embodiment, a separation cover 2 is provided to separate the mixing tank 1 into a mixing chamber 11 and a temporary storage chamber 12. Some materials are ground by the grinding mechanism 5 and enter the mixing tank 1 through the feed port 13. The vibration component 31, the stirring component 32 and the fluidizing component 33 are used to improve the mixing and filling efficiency and the mixing and filling effect of the materials. At the same time, the guide component 34 is used to guide the mixed materials to the temporary storage chamber 12 for temporary storage, which is convenient for step-by-step mixing. In addition, the fluidizing component 33 cooperates with the screening component to remove dust and screen some materials, which is beneficial to subsequent mixing and filling operations.

[0056] In detail, when in use, the microporous ceramic is filled into the screening mechanism 4, the fluidizing component 33 is started to move the microporous ceramic in the screening mechanism 4 to collide with the microporous ceramic to shake out the dust in the micropores 6, and then the dust is screened out of the screening mechanism 4 with the airflow and then led out of the mixing tank 1; then the screened microporous ceramic and conductive carbon black are filled into the mixing chamber 11 and mixed and filled with the vibration component 31, the stirring component 32 and the fluidizing component 33, and then the conductive fiber is added to uniformly mix the three into a first mixture, and the mixed second mixture is passed through the guide component 34. A mixed material is guided to the temporary storage chamber 12 for temporary storage in a fluidized state; then the lead powder, nucleating agent, dispersant and activated carbon are ground finely by the grinding mechanism 5 and filled into the mixing chamber 11 for stirring and mixing by the stirring component 32 to form a second mixed material; finally, the first mixed material in the temporary storage chamber 12 is added to the mixing chamber 11 and the vibration component 31, the stirring component 32 and the fluidization component 33 are used to achieve uniform mixing of the first mixed material and the second mixed material, and then the mixed materials are combined into a mixed material and discharged through the discharge port 14 of the mixing tank 1.

[0057] It should be noted that two feed ports 13 are provided at the upper end of the mixing tank 1, one feed port 13 is connected to the grinding mechanism 5 and is used to fill the mixing tank 1 with materials that need to be ground, and the other feed port 13 is used to fill the mixing tank 1 with materials that do not need to be ground;

[0058] In addition, the grinding mechanism 5 for grinding the material into powder is a prior art and will not be described in detail here.

[0059] Further, if Figure 3-Figure 4 As shown, the vibration assembly 31 includes a vibration cover 311 reciprocatingly arranged at the bottom of the mixing tank 1, a sealing cover 312 arranged between the vibration cover 311 and the mixing tank 1 and used to form a seal therebetween, and a vibrator 313 arranged outside the mixing tank 1 and used to drive the vibration cover 311 to reciprocate and vibrate, and the vibrator 313 is able to drive the vibration cover 311 to move to abut against the partition cover 2 to seal the lower end of the temporary storage chamber 12.

[0060] In this embodiment, a vibrator 313 is provided to drive the vibration cover 311 formed by the sealing cover 312 to move and vibrate, thereby achieving a vibration effect on the material. At the same time, the moving vibration cover 311 can control the opening and closing of the lower end of the temporary storage chamber 12, thereby achieving temporary storage and withdrawal of the material in the temporary storage chamber 12.

[0061] It should be noted that the discharge port 14 of the mixing tank 1 is formed on the vibration cover 311, and the vibration of the vibration cover 311 and the stirring of the stirring assembly 32 are coordinated to facilitate the discharge of the material;

[0062] In addition, the vibrator 313 itself and the installation method are both existing technologies and will not be described in detail here.

[0063] Further, if Figure 5 as well as Figure 7 As shown, the stirring assembly 32 includes a shaft 321 rotatably arranged on the axis of the vibration cover 311, a plurality of stirring blades 322 arranged at equal intervals along the circumference of the mixing tank 1 on the shaft 321 located inside the vibration cover 311, and a driving member 323 arranged outside the vibration cover 311 and used to drive the shaft 321 to rotate.

[0064] In this embodiment, a driving member 323 is provided to drive the stirring blade 322 to rotate along with the shaft 321 to achieve a stirring function.

[0065] It should be noted that the present application does not limit the specific structure of the driving member 323, which can be driven by a motor in conjunction with a gear set or a belt to avoid interference with the end of the shaft 321 connecting to the fluidizing assembly 33. The driving member 323 and its installation method are both existing technologies and will not be described in detail here.

[0066] Further, if Figure 5 as well as Figure 7 As shown, the fluidizing assembly 33 includes an air inlet channel 331 formed on the axis of the shaft 321, an air outlet channel 332 penetrating the stirring blade 322 and connected to the air inlet channel 331, and a rotary joint 333 arranged on the shaft 321 and connected to the air inlet channel 331 and an external negative pressure pipe 334.

[0067] In this embodiment, by setting the air inlet channel 331 on the shaft 321 and the air outlet channel 332 on the stirring blade 322, in conjunction with the rotating joint 333, the air flow formed by the negative pressure pipe 334 is evenly blown toward the bottom of the vibration cover 311 as the stirring blade 322 rotates, stirring and blowing are carried out simultaneously, and the fluidization effect and the mixing effect are good.

[0068] It should be noted that the negative pressure pipe 334 inputs gas into the air inlet channel 331 through the negative pressure device. The negative pressure device and the rotating structure itself and the installation method are all existing technologies and will not be described in detail here.

[0069] Further, if Figure 6-Figure 7 As shown, the guide assembly 34 includes a guide hood 341 arranged at the upper end of the partition hood 2, a plurality of driving rods 342 which are rotatably arranged at the upper end of the partition hood 2 at equal intervals along the circumference of the mixing tank 1 and rotate toward the inside and outside of the mixing chamber 11 in cooperation with the airflow formed by the fluidization assembly 33 and its own gravity, and a shielding hood 343 which is arranged on the inner wall of the mixing tank 1 and is used to block the gap between the guide hood 341 and the mixing tank 1 when the guide hood 341 rotates into the mixing chamber 11.

[0070] In this embodiment, the driving rod 342 is arranged to rotate with the airflow formed by the fluidizing component 33 and its own gravity to cause the guide cover 341 to rotate, thereby guiding the material to the mixing chamber 11 or the temporary storage chamber 12. At the same time, when the guide cover 341 guides the material into the mixing tank 1, the shielding cover 343 is used to block the gap between the guide cover 341 and the mixing tank 1 to prevent the newly added material from directly entering the temporary storage chamber 12.

[0071] In detail, when adding materials, the fluidizing component 33 is closed, and the driving rod 342 rotates into the mixing chamber 11 under the action of gravity, and then the inner end of the guide cover 341 rotates into the mixing chamber 11 and the outer end rotates to the bottom of the shielding cover 343, so that the materials can enter the mixing chamber 11 after being guided by the shielding cover 343 and the guide cover 341; when the materials are temporarily stored, the fluidizing component 33 is opened, and the airflow blows the inner end of the guide cover 341 to rotate out of the mixing chamber 11 and the outer end rotates into the temporary storage chamber 12, and then the fluidized materials enter the temporary storage chamber 12 after being guided by the shielding cover 343 and the guide cover 341.

[0072] It should be noted that the sealing cover 312 and the air guide cover 341 are made of rubber or latex and have good ductility and deformation ability.

[0073] Further, if Figure 2-Figure 3 as well as Figure 8-Figure 11 As shown, two screening ports 15 are provided through the mixing tank 1 at intervals;

[0074] The screening mechanism 4 includes two screens 41 which are respectively movably arranged in the two screening ports 15 and form a screening cavity 411 in the mixing tank 1, two sealing components 42 which are respectively arranged in the two screening ports 15 and used to form a seal between the screening ports 15 and the screens 41, and two driving components 43 which are arranged outside the mixing tank 1 and used to drive the screens 41 to move and form a seal with the sealing components 42, and the hole diameter of the lower screen 41 is smaller than the hole diameter of the upper screen 41.

[0075] In this embodiment, two screens 41 are provided in cooperation with a sealing assembly 42 and a driving assembly 43 to control the opening and closing of the screening chamber 411 and the sealing of the mixing tank 1, thereby achieving material screening while avoiding material leakage.

[0076] In detail, when the microporous ceramic is dusted, the upper screen 41 is moved out of the screening port 15 to open the screening chamber 411 and then the microporous ceramic is filled in. Then the upper screen 41 is moved into the screening port 15 to close the screening chamber 411. The airflow formed by the fluidizing component 33 forces the microporous ceramic to move and collide to shake out the dust in the micropores 6. Then the dust is screened out through the upper screen 41 and led out of the mixing tank 1 to complete the dust removal operation. Finally, the fluidizing component 33 is closed, and the lower screen 41 is moved out of the screening port 15 to open the screening chamber 411, so that the microporous ceramic is filled into the mixing chamber 11. When the fluidizing component 33 performs fluidized mixing, the lower screen 41 is moved into the screening port 15 to prevent the fluidized material from leaking out of the mixing tank 1.

[0077] It should be noted that a lifting rod 344 is provided on the driving rod 342. On the one hand, when the deflector 341 rotates out of the mixing chamber 11, the lifting rod 344 can lift the screen 41, and the screen 41 can guide the material toward the temporary storage chamber 12, thereby improving the guiding effect on the material. On the other hand, the self-weight of the driving rod 342 is increased to facilitate rotation under the action of gravity.

[0078] Further, if Figure 8-Figure 11 As shown, the sealing assembly 42 includes a mounting frame 421 disposed outside the mixing tank 1, two sealing airbags 422 disposed on both sides of the sieve hole, and two groups of driving airbags 423 disposed on both sides of the mounting frame 421 and connected to the two sealing airbags 422;

[0079] The driving assembly 43 includes a winding roller 431 rotatably set on the mounting frame 421 and used for winding up one end of the screen 41, two screw rods 432 and a sliding rod 436 set on the mounting frame 421 and respectively located on both sides of the screen 41, a slider 433 connected to the screw rod 432 and the sliding rod 436 and used for pressing the driving airbag 423, a mounting block 434 slidably set on the slider 433 and used for installing and fixing the screen 41 away from one end of the winding roller 431, and an elastic member 435 set on the slider 433 and used for forcing the mounting block 434 to move away from the screen 41. When the mounting block 434 moves with the slider 433 to pull the screen 41 into the screening port 15, the mounting frame 421 limits the sliding of the mounting block 434, and the slider 433 continues to move to squeeze a driving airbag 423.

[0080] In this embodiment, a slider 433 is provided to cooperate with the winding roller 431 to control the screen 41 from entering and exiting the screening port 15, and at the same time cooperate with two groups of driving airbags 423. When the screen 41 enters and exits the screening port 15, the slider 433 is able to squeeze one group of driving airbags 423 so that the sealing airbag 422 bulges to seal the screening port 15. In addition, with the assistance of the mounting block 434 and the elastic member 435, when the screen 41 moves into the screening port 15, the mounting frame 421 forces the screen 41 to stop moving with the mounting block 434, the elastic member 435 is deformed, and the slider 433 is able to continue to move to squeeze the driving airbag 423 so that the sealing airbag 422 bulges until the screen 41 is clamped. When the screen 41 moves out of the screening port 15, the elastic member 435 restores its deformation to force the mounting block 434 to reset on the slider 433.

[0081] It should be noted that the elastic member 435 is a coil spring, a leaf spring, etc., and both the elastic member 435 and the installation method thereof are existing technologies and will not be described in detail here.

[0082] Embodiment 3

[0083] like Fig.11 As shown, a method for preparing the above-mentioned lead-carbon battery negative electrode material for power energy storage comprises the following steps:

[0084] Step 1: Filling process, mixing the microporous ceramic and the conductive carbon black, and evenly filling the conductive carbon black into the micropores 6 of the microporous ceramic, adding the conductive fiber, and evenly mixing the three into a first mixture;

[0085] Step 2: a mixing process, wherein the lead powder, the nucleating agent, the dispersant and the activated carbon are uniformly mixed into a second mixed material, and then the first mixed material and the second mixed material are uniformly mixed into a mixed material;

[0086] Step 3: Mixing process: take lead powder and put it into the vacuum paste machine together with the mixed materials, then add sulfate and adhesive, and start stirring for 10 minutes to mix;

[0087] Step 4: Paste mixing process. After mixing, slowly add water into the vacuum paste machine within 3 minutes and continue stirring for 5 minutes to adjust the plasticity to form a lead paste of the negative electrode material of the lead-carbon battery for power storage, which can then be filled and used.

[0088] It should be noted that the vacuum and paste machines themselves and their installation methods are all existing technologies and will not be described in detail here.

[0089] Further, if Figure 7As shown, in step one and step two, the first mixture and the second mixture are mixed in the same mixing device, and a mixing chamber 11 and a temporary storage chamber 12 are formed in the mixing device. After the first mixture is mixed in the mixing chamber 11, it is temporarily stored in the temporary storage chamber 12. When the second mixture is mixed in the mixing chamber 11, the first mixture in the temporary storage chamber 12 enters the mixing chamber 11 for mixing.

[0090] Further, if Figure 1 as well as Figure 7 As shown, in step one, the microporous ceramic and the conductive carbon black are fluidized and mixed with vibration filling, and the conductive carbon black is vibrated and filled into the micropores 6 of the microporous ceramic while being mixed, and the fluidized first mixture is conveniently collected and temporarily stored in the temporary storage chamber 12.

[0091] Further, if Figure 7 As shown, in step 2, lead powder, nucleating agent, dispersant and activated carbon are mixed by stirring to achieve mixing while preventing the materials from being lifted up and entering the temporary storage chamber 12 in large quantities. The first mixture and the second mixture are mixed by stirring and fluidizing to achieve rapid and uniform mixing of the mixed materials.

[0092] Furthermore, in step one, the microporous ceramic is subjected to dust removal before being mixed with the conductive carbon black to remove dust in the microporous ceramic.

[0093] Furthermore, in step 2, the lead powder, the nucleating agent, the dispersant and the activated carbon are ground and then mixed.

[0094] In the description of the present invention, it is necessary to understand that the directions or positional relationships indicated by the terms "front and back", "left and right", etc. are based on the directions or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or component referred to must have a specific direction, be constructed and operated in a specific direction, and therefore cannot be understood as a limitation on the invention.

[0095] Of course, in the present technical solution, those skilled in the art should understand that the term "one" should be understood as "at least one" or "one or more", that is, in one embodiment, the number of an element may be one, while in another embodiment, the number of the element may be multiple, and the term "one" should not be understood as a limitation on the quantity.

[0096] The above is only a preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art under the technical guidance of the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A method for preparing a negative electrode material of a lead-carbon battery for power storage, characterized in that: The following steps are involved: Step 1: a filling process, mixing the microporous ceramic and the conductive carbon black, and evenly filling the conductive carbon black into the micropores of the microporous ceramic, and then adding the conductive fiber, and evenly mixing the three into a first mixture; Step 2: a mixing process, wherein the lead powder, the nucleating agent, the dispersant and the activated carbon are uniformly mixed into a second mixed material, and then the first mixed material and the second mixed material are uniformly mixed into a mixed material; Step 3: Mixing process: take lead powder and put it into the vacuum paste machine together with the mixed materials, then add sulfate and adhesive, and start stirring for 10 minutes to mix; Step 4: Paste mixing process: after the mixing is completed, water is slowly added to the vacuum paste machine within 3 minutes and the plasticity is adjusted while continuously stirring for 5 minutes to form the lead paste of the negative electrode material of the lead-carbon battery for power energy storage, which is then filled and used; The lead-carbon battery negative electrode material for power energy storage comprises: 100 parts of lead powder, 6-10 parts of sulfate, 1-2 parts of mixed materials, 0.5-1 parts of CMC adhesive and 8-15 parts of water; The mixed material comprises 1-3 parts of microporous ceramic, 2-5 parts of conductive carbon black, 0.5-1 parts of conductive fiber, 2-5 parts of lead powder, 3-8 parts of nucleating agent, 1-3 parts of dispersant and 0.5-1 parts of activated carbon; The sulfate includes 3-8 parts of tribasic lead sulfate and 4-15 parts of tetrabasic lead sulfate.

2. The method for preparing a negative electrode material of a lead-carbon battery for power storage according to claim 1, characterized in that: In step 1 and step 2, the first mixture and the second mixture are mixed in the same mixing equipment, and a mixing chamber and a temporary storage chamber are formed in the mixing equipment. After the first mixture is mixed in the mixing chamber, it is temporarily stored in the temporary storage chamber. After the second mixture is mixed in the mixing chamber, the first mixture in the temporary storage chamber enters the mixing chamber again for mixing.

3. The method for preparing a negative electrode material of a lead-carbon battery for power storage according to claim 2, characterized in that: In step one, the microporous ceramic and the conductive carbon black are fluidized and mixed with vibration filling, and the conductive carbon black is vibrated and filled into the micropores of the microporous ceramic while being mixed, and the fluidized first mixture is conveniently collected and temporarily stored in the temporary storage chamber.

4. The method for preparing a negative electrode material of a lead-carbon battery for power storage according to claim 3, characterized in that: In step 2, lead powder, nucleating agent, dispersant and activated carbon are mixed by stirring to achieve mixing while preventing the materials from being lifted up and entering the temporary storage chamber in large quantities. The first mixture and the second mixture are mixed by stirring and fluidizing to achieve rapid and uniform mixing of the mixed materials.

5. The method for preparing a negative electrode material of a lead-carbon battery for power storage according to claim 4, characterized in that: In step one, before mixing the microporous ceramic and the conductive carbon black, the microporous ceramic is subjected to a dust removal operation to remove dust in the microporous ceramic.

6. The method for preparing a negative electrode material of a lead-carbon battery for power storage according to claim 1, characterized in that: In step 2, lead powder, nucleating agent, dispersant and activated carbon are ground and then mixed.

7. A lead-carbon battery negative electrode material for power energy storage prepared by the method for preparing a lead-carbon battery negative electrode material for power energy storage according to any one of claims 1 to 6, characterized in that: include: 100 parts of lead powder, 6-10 parts of sulfate, 1-2 parts of mixed materials, 0.5-1 parts of CMC adhesive and 8-15 parts of water; The mixed material comprises 1-3 parts of microporous ceramics, 2-5 parts of conductive carbon black, 0.5-1 parts of conductive fibers, 2-5 parts of lead powder, 3-8 parts of nucleating agents, 1-3 parts of dispersants and 0.5-1 parts of activated carbon.

8. The lead-carbon battery negative electrode material for power storage according to claim 7, characterized in that: The microporous ceramic is a spherical porous ceramic, the diameter of the microporous ceramic is 95um-105um, and the pore size of the micropores on the microporous ceramic is 5um-50um.

9. The lead-carbon battery negative electrode material for power storage according to claim 7, characterized in that: The nucleating agent is barium sulfate, and the dispersing agent is sodium lignin sulfate.

Citation Information

Patent Citations

  • Negative lead paste for lead carbon battery and negative plate

    CN108630937A

  • Lead-acid storage battery negative electrode lead paste and preparation method thereof

    CN108832080A

  • Lead-carbon battery negative electrode lead paste and preparation method thereof

    CN110993896A

  • Polar cavity type graphene lead-acid storage battery

    CN111211258A